2022
DOI: 10.1155/2022/9165651
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Outcomes between Two Surgical Techniques for Patients with Intestinal Neuronal Dysplasia

Abstract: Objective. Hirschsprung disease (HSCR) is a serious congenital intestinal disease with a prevalence of 1/5000. HSCR remains one of the most severe congenital malformations of the abdominal organs in children that require complex reconstructive surgery. This study is aimed at investigating the clinical analysis of ileal Santulli stoma and ileal double-lumen stoma in children diagnosed with intestinal neuronal dysplasia (IND). Methods. Retrospective analysis was performed on the children who were admitted to our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Conservative therapy is composed of changes in diet, laxatives, and enemas in cases of fecal retention [ 4 , 19 , 20 ]. Surgical treatment includes sphincterotomy, extensive surgical resection, or temporary colostomy [ 21 , 22 , 23 , 24 , 25 ]. The current recommendation is that patients with no complications receive conservative treatment [ 4 , 7 , 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative therapy is composed of changes in diet, laxatives, and enemas in cases of fecal retention [ 4 , 19 , 20 ]. Surgical treatment includes sphincterotomy, extensive surgical resection, or temporary colostomy [ 21 , 22 , 23 , 24 , 25 ]. The current recommendation is that patients with no complications receive conservative treatment [ 4 , 7 , 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, histopathological changes compatible with the diagnosis of IND-B were found in the colon segments of 36 completely asymptomatic children [ 26 ]. Other studies have failed to demonstrate a direct correlation between histopathological findings, clinical symptoms, and radiological and manometric changes [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Faced with these controversies, several authors do not consider IND-B as a true clinical entity but only as a histopathological alteration of the enteric nervous system that may or may not present symptoms [ 16 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%